Exercise intervention in people with cancer undergoing adjuvant cancer treatment following surgery: A systematic review. Issue 12 (December 2015) - Loughney, L.; West, M.A.; Kemp, G.J.; Grocott, M.P.W.; Jack, S.
Abstract: Background: Remaining physically active during and after cancer treatment is known to improve associated adverse effects, improve overall survival and reduce the probability of relapse. This systematic review addresses the question: is an exercise training programme beneficial in people with cancer undergoing adjuvant cancer treatment following surgery. Methods: A systematic database search of Embase, Ovid, Medline without Revisions, SPORTDiscus, Web of Science, Cochrane Library andClinicalTrials.gov for any randomised controlled trials (RCT) or non-RCT addressing the effect of an exercise training programme in those having adjuvant cancer treatment following surgery was conducted. Results: The database search yielded 6489 candidate abstracts of which 94 references included the required terms. A total of 17 articles were included in this review. Exercise training is safe and feasible in the adjuvant setting and furthermore may improve measures of physical fitness and health related quality of life (HRQoL). Conclusion: This is the first systematic review on exercise training interventions in people with cancer undergoing adjuvant cancer treatment following surgery. Due to the lack of adequately powered RCTs in this area, it remains unclear whether exercise training in this context improves clinical outcomes other physical fitness and HRQoL. It remains unclear what is the optimal timing of initiation of an exercise programme and what are the best combinations of elements within an exercise training programme to optimise training efficacy. Furthermore, it is unclear if initiating such exercise programmes at cancer diagnosis may have a long-lasting effect on physically activity throughout the subsequent life course.